Abdominal lymph node recurrence from colorectal cancer: Resection should be considered as a curative treatment in patients with controlled disease. (December 2020) - Zarzavadjian Le Bian, Alban; Genser, Laurent; Tabchouri, Nicolas; Fillol, Clari; Laforest, Anais; Tresallet, Christophe; Ouaissi, Mehdi; Fuks, David
Abstract: Background: Lymph node recurrences (LNR) from colorectal cancer (CRC) still represent a therapeutic challenge, as standardized recommendations have yet to be established. The aim of this study was to analyze short- and long-term oncological outcomes following resection of LNR from CRC. Methods: All patients with previously resected CRC who underwent histopathologically confirmed LNR resection in 3 tertiary referral centers between 2010 and 2017 were reviewed. Short- and long-term outcomes were analyzed, mainly recurrence-free and overall survival. Further recurrences following LNR resection were also analyzed. Results: Overall, 18 patients were included. Primary CRC was left-sided in 16 (89%) patients, staged T3-4 in 15 (83%), N+ in 14 (78%) and presented with synchronous metastases in 8 (43%). Median time interval between primary CRC and LNR resections was 31 months. Performed lymphadenectomies were aortocaval (n = 10), pelvic (n = 7), in hepatic pedicle (n = 3) and mesenteric (n = 1). Four patients had associated liver metastases resection. Three (17%) presented with postoperative complications, of which one Clavien-Dindo 3. Fourteen (78%) patients presented with further recurrences after a mean delay of 9 months, with 36% of patients presenting with early (<6 months) recurrence. Five (36%) patients could undergo secondary recurrence resection and 3 (21%) patients radiotherapy. Median overall survival following LNR resection reached 44 months. Conclusions: Current results suggest that LNR resection is feasible and associated with improved survival, in selected patients. Longer time interval between primary CRC resection and LNR occurrence appeared to be a favorable prognostic factor whereas multisite recurrence appeared to be associated with impaired long-term survival. Highlights: Lymph node recurrences from colorectal cancer represent a therapeutic challenge. A multicentric retrospective series of resection is reported and analyzed. Resection of lymph node recurrence is associated with improved survival, in selected patients.